PECULIARITIES OF ANALYZING THE COMPETITIVE ADVANTAGES OF AN ENTERPRISE IN CONDITIONS OF UNCERTAINTY - Bril, MYKHAILO; SHMALKO, Elizaveta (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The development of competitive advantages in a complex environment characterized by a high level of uncertainty is becoming a challenge and at the same time a necessity for enterprises. Adaptive management and innovation have become key to the struggle for competitive advantages. The article aims to study modern models of competitive advantage analysis, substantiate practical recommendations for their use, and identify the main factors of uncertainty that affect the activities of enterprises.The article considers the main aspects of analyzing the competitive advantages of an enterprise in conditions of constant market uncertainty. The importance of strategic management and the need for enterprises to adapt to changes are described. Particular attention is paid to using strategic analysis tools that are appropriate to use when analyzing competitive advantages, as well as assessing their advantages, disadvantages, and limitations. Recommendations are proposed to strengthen the competitive positions of enterprises in a changing market environment, which are associated with: regular strategic analysis; increasing the potential for investing in innovation to increase adaptability; gradual technologization of management and modernization of production; development and implementation of a diversification strategy to reduce risks; assessing the feasibility of creating a new product and areas for reducing the intensity of competition in the B2C and B2B markets.It has been proven that enterprises ready to adapt their strategies, invest in innovation, and actively analyze the external environment have a better chance of success in uncertain conditions. Most of the above risks are uncertainty and insufficient ownership of innovative components. A systematic approach to managing competitive advantages is a key factor in ensuring the sustainability and development of an enterprise in the modern market.
Keywords: competitive advantages; uncertainty; strategic analysis; adaptive management; strategic planning; innovation